Alternative perimetric tests for patients with drug-resistant epilepsy. - Monika Thakur; Abhinay Kumar Gattu; Jagarlapudi M K Murthy; PremNandhini Satgunam (PLoS ONE)
Objective Visual field assessment is an important presurgical test for patients with drug-resistant epilepsy (DRE), particularly with posterior cortex epilepsy. However, the assessment using conventional perimeters like Humphrey Visual Field Analyzer (HFA) may not always be feasible in some patients. This study aims to determine if alternative methods like tangent screen perimetry or Baby Vision Screener (BaViS) can be used for such patients. Methods This retrospective study included 17 patients (mean age: 18 ±  8.7, range: 6 to 38 years) with DRE. Visual fields were attempted first with HFA and then with one or both alternative methods, by different examiners. Visual field extent was measured using the kinetic perimetry mode in the alternative methods. With HFA, kinetic and/or static perimetry was attempted. Results Only 12% of the patients were able to perform the HFA. Whereas the testability of BaViS was 91% and tangent screen perimetry was 87%. Comparable visual field isopters were obtained on one patient on whom all the 3 tests could be performed, and in two patients on whom at least two tests could be performed reliably. For one patient, visual field isopters could not be quantified on any device. In this patient, a gross visual field assessment was possible using BaViS. Conclusion BaViS or tangent screen perimeter can be used to quantify visual field defects in patients with DRE when conventional perimetry is not possible. Such an approach may help the clinician in assessing the suitability of patients with DRE and visual field deficits, for epilepsy surgery.